Characteristics of Serum Thyroid Hormones in Different Metabolic Phenotypes of Obesity - Nie, Xiaomin; Ma, Xiaojing; Xu, Yiting; Shen, Yun; Wang, Yufei; Bao, Yuqian (Frontiers in Endocrinology, 2020)
Aim: Metabolically healthy obese (MHO) individuals have attracted broad attention. We aimed to investigate the characteristics of serum thyroid hormones in different metabolic phenotypes of obesity. Methods: The study included 1023 community-based euthyroid subjects (age range: 27-81 years), of which 586 were women. Fat% was detected by a bioelectrical impedance analyzer. Two definitions of obesity were applied as follows: 1. fat% ≥ 25% for men and ≥ 30% for women; 2. body mass index (BMI) ≥ 25 kg/m2. According to the diagnostic criteria for metabolic syndrome by the Chinese Diabetes Society, metabolically unhealthy was defined as two or more components of metabolic syndrome, excluding waist circumference. Serum free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) levels were measured by electrochemiluminescence immunoassay. Results: The proportions of obesity defined by fat% and BMI were 41.3% and 27.1%, respectively. The proportion of metabolically unhealthy was 41.6%. After adjusting for age and gender, regardless of the definitions based on fat% or BMI, FT3 was positively related to both the MHO and the metabolically unhealthy obese (MUO) phenotypes [MHO: odds ratio (OR)s = 1.676 based on fat% and 2.055 based on BMI; MUO: ORs = 1.818 based on fat% and 1.526 based on BMI; all P < 0.05]; FT4 was negatively related to the MUO phenotype (ORs = 0.870 based on fat% and 0.849 based on BMI, all P < 0.05); FT3/FT4 was also positively related to both the MHO and the MUO phenotypes (MHO: ORs = 1.678 based on fat% and 2.825 based on BMI; MUO: ORs = 2.866 based on fat% and 2.883 based on BMI; all P < 0.05); and TSH was positively related to the metabolically unhealthy non-obese phenotype (ORs = 1.329 based on fat% and 1.321 based on BMI, all P < 0.01). Conclusions: In euthyroid population, both the MHO and the MUO phenotypes were characterized by increased FT3 and FT3/FT4 levels.